The dragon prince. [2], Bloodmoon huntress - Ehasz, Aaron; Ehasz, Aaron; Andelfinger, Nicole; Richmond, Justin; Richmond, Justin (Dragon prince (Graphic novel series), 2022)
"Every Moonshadow elf child knows the scary stories of the Bloodmoon Huntress, the evil sorceress who steals your blood on the night of the Harvest Moon. Everyone also knows those legends aren't true. But for young Rayla, whose parents recently left her behind to fulfill their duty as members of the elite Dragonguard, this autumn is scarier than most. Her guardians, Runaan and Ethari, are still getting the hang of the whole parenting thing, and no one will tell Rayla what Runaan does for a living. She spends most of her time exploring the forest outside the Silvergrove. When Rayla discovers a young Skywing elf in danger just hours before the Harvest Moon will rise, the scary stories become real. Can she stop the Huntress before the moon reaches its zenith?"--Back cover